The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1034/j.1600-051x.2001.028006517.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental peri‐implant mucositis in man

Abstract: The results of the present study indicated that plaque accumulation induced an inflammatory response characterized by increased proportions of T- and B-cells in the ICT of both the gingiva and the PiM. Although not statistically significant, the host response in the gingiva tended to be more pronounced than in the peri-implant mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
223
2
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(257 citation statements)
references
References 16 publications
20
223
2
12
Order By: Relevance
“…Тем не менее из-за отсутствия це-мента -одного из компонентов биологической ширины -отмечаются специфическая ориентация соединитель-нотканных волокон и иная структура прикрепления к по-верхности ДИ [49,74]. Значительное уменьшение количе-ства составных элементов дает основание охарактеризо-вать тканевой слой, формируемый непосредственно в окружности введенного ДИ, как фиброзный, со снижен-ной способностью реагировать на раздражение [93]. Кро-ме того, объемные параметры ПИТ в некоторой степени зависят от состояния прилегающих мягких тканей [74,79].…”
Section: стоматология 2 2015unclassified
“…Тем не менее из-за отсутствия це-мента -одного из компонентов биологической ширины -отмечаются специфическая ориентация соединитель-нотканных волокон и иная структура прикрепления к по-верхности ДИ [49,74]. Значительное уменьшение количе-ства составных элементов дает основание охарактеризо-вать тканевой слой, формируемый непосредственно в окружности введенного ДИ, как фиброзный, со снижен-ной способностью реагировать на раздражение [93]. Кро-ме того, объемные параметры ПИТ в некоторой степени зависят от состояния прилегающих мягких тканей [74,79].…”
Section: стоматология 2 2015unclassified
“…Onderzoek heeft laten zien dat, uitgaande van een gezonde situatie, 3 weken ongestoorde plaque-accumulatie rond een implantaat leidt tot ontstekingslaesies in de zachte periimplantaire weefsels (Zitzmann et al, 2001). Als deze ontsteking langer bestaat, kan dit leiden tot een ontstekingsproces waarbij het peri-implantaire bot wordt aangetast (Berglundh et al, 2004).…”
Section: Peri-implantaire Infectiesunclassified
“…Moreover, the extent of bacterial adhesion has been shown to correlate directly with the extent of surface roughness [5]. Several authors have shown that methods which increase surface roughness resulted in enhanced attachment of bacteria [6,7]. Biofilms then develop quickly and mature rapidly, nourished by nutrients from the host, both through saliva and through gingival crevicular fluid and blood.…”
Section: Biofilm Development On Implant Surfacesmentioning
confidence: 99%